2009
DOI: 10.3727/096368909x12483162197240
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic Effect of Tacrolimus on Cytokine-Challenged Human Islets

Abstract: Our goal was to investigate whether previously related antiapoptotic and anti-inflammatory effects of tacrolimus could be useful in protecting human islets cultured in the presence of several proinflammatory mediators. Human islets obtained from cadaveric donors after intraductal infusion with collagenase, mechanical digestion, and continuous Ficoll gradient purification were cultured in RPMI-1640 medium for 24 h. Escherichia coli lipopolysaccharide (10 microg/ml) or interleukin-1 (50 UI/ml) + gamma-IF (1000 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Tacrolimus has been shown to promote the generation of reactive oxygen species, mitochondrial dysfunction and apoptosis in Jurkat T-cells[ 8 ]. By contrast, tacrolimus has an anti-apoptotic effect in human islet cells treated with pro-inflammatory cytokines, causing a reduction in TNF-α and down-regulation of caspase-3[ 22 ]. In the current study we found that at therapeutically relevant concentrations, neither cyclosporine nor tacrolimus promoted hepatocyte cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus has been shown to promote the generation of reactive oxygen species, mitochondrial dysfunction and apoptosis in Jurkat T-cells[ 8 ]. By contrast, tacrolimus has an anti-apoptotic effect in human islet cells treated with pro-inflammatory cytokines, causing a reduction in TNF-α and down-regulation of caspase-3[ 22 ]. In the current study we found that at therapeutically relevant concentrations, neither cyclosporine nor tacrolimus promoted hepatocyte cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation could therefore illustrate a reciprocal inhibition of the two drugs [ 13 ] or that maximum intervention has been reached. Others have shown that sirolimus and tacrolimus have anti-inflammatory properties [ 44 47 ]. Compared to our data they use longer exposure time and lower drug dose, which are reasonable explanations for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, short-term administration of tacrolimus has been shown to have no effect on islet secretion in healthy human subjects and improves beta cell viability and function when islets are under stress [102,104,105]. Indeed, acute exposure of tacrolimus prevents apoptosis in islets exposed to cytokines in vitro and can restore insulin gene transcription in islets chronically exposed to high glucose within a 48 h window [106,107]. Furthermore, short-term peptide inhibition of the CN downstream target NFAT in islets was shown to prolong graft function in an allogeneic mouse transplant model.…”
Section: Strategies To Prevent Islet-immune Cell Mediated Loss Of Islmentioning
confidence: 99%